Illicit Opioid Intoxication: Diagnosis and Treatment - A. Fareed; S. Stout; J. Casarella; S. Vayalapalli; J. Cox; K. Drexler (SAGE Publishing, 2011)
Opioid intoxications and overdose are associated with high rates of morbidity and mortality. Opioid overdose may occur in the setting of intravenous or intranasal heroin use, illicit use of diverted opioid medications, intentional or accidental misuse of prescription pain medications, or iatrogenic overdose. In this review, we focused on the epidemiology of illict opioid use in the United States and on the mechanism of action of opioid drugs. We also described the signs and symptoms, and diagnoses of intoxication and overdose. Lastly, we updated the reader about the most recent recommendations for treatment and prevention of opioid intoxications and overdose.